KEDUDUKAN DAN PERLINDUNGAN HUKUM SAKSI SEBAGAI ALAT BUKTI YANG SAH DALAM PROSES PERADILAN PIDANA DI INDONESIA - Umi Enggarsasi (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2007)
Valid Appliance Evidence according to Section 184 KUHAP in the form of eyewitness boldness, expert boldness, letter guide, defendant boldness, In process protection of eyewitness boldness represent valid evidence appliance which its inspection first, while protection of eyewitness law according to Law of No. 13 Year 2006 have ground, standing or appreciation and human being prestige, feel safe, justice, do not rule of law and discriminative, Institute Protection Eyewitness and Victim represent lifted by institute is President, in charge of to handle giving of aid and Protection at victim and eyewitness.